Pengaruh Kemajuan Teknologi Informasi Terhadap Perkembangan Akuntansi - Afifah Rahmadini; Zulkarnain Zulkarnain (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
The rapid advancement in information technology has transformed the landscape of accounting, making it increasingly computerized, enhancing efficiency through the automation of routine tasks, enabling real-time access to financial data, and providing more sophisticated data analytics capabilities. However, alongside these benefits, technology also brings challenges related to data security and changing regulations, necessitating accountants to continuously develop their technological skills. Online collaboration between accountants and clients is becoming more common, reflecting the influence of information technology on the evolution of accounting practices. Technological developments also affect Accounting Information Systems (AIS), changing the way data is processed, internal controls are implemented, and financial information is prepared. Despite initial concerns, the advancement of IT ultimately opens up new opportunities, such as computer-based information system audits, computer-based information system consulting, and web trust audits. This is the essence of the impact of information technology on the development of accounting, presenting opportunities and challenges that require adaptation and a strong understanding from accounting professionals in the digital era.